Na(V)1.5 sodium channel window currents contribute to spontaneous firing in olfactory sensory neurons - Frenz, Christopher T. (American Physiological Society, 2014)
Olfactory sensory neurons (OSNs) fire spontaneously as well as in response to odor; both forms of firing are physiologically important. We studied voltage-gated Na(+) channels in OSNs to assess their role in spontaneous activity. Whole cell patch-clamp recordings from OSNs demonstrated both tetrodotoxin-sensitive and tetrodotoxin-resistant components of Na(+) current. RT-PCR showed mRNAs for five of the nine different Na(+) channel α-subunits in olfactory tissue; only one was tetrodotoxin resistant, the so-called cardiac subtype Na(V)1.5. Immunohistochemical analysis indicated that Na(V)1.5 is present in the apical knob of OSN dendrites but not in the axon. The Na(V)1.5 channels in OSNs exhibited two important features: 1) a half-inactivation potential near −100 mV, well below the resting potential, and 2) a window current centered near the resting potential. The negative half-inactivation potential renders most Na(V)1.5 channels in OSNs inactivated at the resting potential, while the window current indicates that the minor fraction of noninactivated Na(V)1.5 channels have a small probability of opening spontaneously at the resting potential. When the tetrodotoxin-sensitive Na(+) channels were blocked by nanomolar tetrodotoxin at the resting potential, spontaneous firing was suppressed as expected. Furthermore, selectively blocking Na(V)1.5 channels with Zn(2+) in the absence of tetrodotoxin also suppressed spontaneous firing, indicating that Na(V)1.5 channels are required for spontaneous activity despite resting inactivation. We propose that window currents produced by noninactivated Na(V)1.5 channels are one source of the generator potentials that trigger spontaneous firing, while the upstroke and propagation of action potentials in OSNs are borne by the tetrodotoxin-sensitive Na(+) channel subtypes.